Design of Company Inventory Information System Application Based on Microsoft Excel at PT Duta Garmindo Industri Bojong Branch - Thirza Pramudya Sutadipura (Records Management System Journal, 2023)
Effective and efficient work in a company or organization is a very important thing that helps employees do the work quickly and precisely, one of the important things that must be done effectively and efficiently is to get information. The information obtained will be the basis for the company to make a policy decision. Information about assets or inventory in the company is something that needs to be considered,recording the entry and exit of goods is an activity in inventory management, errors in the amount of input or output of inventory data become a thing that often happens, so we need an information system to manage it. PT Duta Garmindo Industri Bojong Branch uses Microsoft Excel lined inventory management system by manually inputting data, starting from adding, and subtracting to summing the inventory calculated manually, this will reduce the effectiveness and efficiency of employees at work. Therefore, it is necessary to upgrade the Microsoft Excel recording system,which includes the dashboard display, the results of adding and subtracting items automatically and accurately. With this upgrade, it is hoped that the human resources in the company can be more effective and efficient in their work.